Primary care providers should prescribe aspirin to prevent cardiovascular disease based on benefit−risk ratio, not age. Issue 4 (24th December 2021) - Kim, Kyungmann; Hennekens, Charles H; Martinez, Lisa; Gaziano, J Michael; Pfeffer, Marc A; Biglione, Bianca; Gitin, Alexander; McCabe, Jeanne Bell; Cook, Thomas D; DeMets, David L; Wood, Sarah K
Abstract : Recent guidelines restricted aspirin (ASA) in primary prevention of cardiovascular disease (CVD) to patients <70 years old and more recent guidance to <60. In the most comprehensive prior meta-analysis, the Antithrombotic Trialists Collaboration reported a significant 12% reduction in CVD with similar benefit−risk ratios at older ages. Using Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, four trials were added to an updated meta-analysis. ASA produced a statistically significant 13% reduction in CVD with 95% confidence limits (0.83 to 0.92) with similar benefits at older ages in each of the trials. Primary care providers should make individual decisions whether to prescribe ASA based on benefit−risk ratio, not simply age. When the absolute risk of CVD is >10%, benefits of ASA will generally outweigh risks of significant bleeding. ASA should be considered only after implementation of therapeutic lifestyle changes and other drugs of proven benefit such as statins, which are, at the very least, additive to ASA. Our perspective is that individual clinical judgements by primary care providers about prescription of ASA in primary prevention of CVD should be based on our evidence-based solution of weighing all the absolute benefits and risks rather than age. This strategy would do far more good for far more patients as well as far more good than harm in both developed and developing countries. This new and novel strategy for primary care providers to consider in prescribing ASA in primary prevention of CVD is the same as the general approach suggested by Professor Geoffrey Rose decades ago.